Utilization of Cu-T in Paschim Midnapur district of West Bengal, India: An appraisal (South East Asia Journal of Public Health, 2014)
As a part of its commitment towards provision of quality spacing services in family planning, the Government of India introduced Cu-T 380A in 2002 with an effective protection for 10 years replacing the earlier Cu-T 200B. In India, the use of the intrauterine device (IUD) is very low among married women of reproductive age, despite the fact that the Government offers IUD (Cu-T) services free of cost. The aim of the study was to assess the current status of intrauterine contraceptive device (Copper-T) utilization and to determine the relevant factors influencing utilization by currently married women of the reproductive age. The community-based cross-sectional study was carried out in 3 Blocks and 2 Municipality areas of the West Midnapur district in West Bengal. A multistage random sampling method was carried out to select villages of sub-center areas and wards from Municipality areas. A total of 16 areas were selected for the purpose of the study; 125 eligible couples from each selected area were interviewed by a house-to-house survey in order to cover 2000 eligible couples throughout the district. Only females were the respondents. It was found that 67.4% of the couples admitted to the use of any method of contraception. The Couple Protection Rate (by modern method) was found to be 62.6% in the study area. However, it was demonstrated that Cu-T acceptance rate was only 1.3%. Ligation (38.8 %) contributed the highest other methods included: oral contraceptive pill (19.4%), condom (3%), vasectomy (0.1%) and others (4.8%). The ever use rate of intrauterine contraceptive device (Cu-T/loop) in the study area was 6.2%, which increased significantly with the advancement of maternal age, but no association was found with literacy status of the respondents. Lack of motivation (48.4%), misconception (14%), unawareness (11.3%) unwillingness (9.3%) and religious/cultural barrier (2.4%) were the major factors for underutilization/non-utilization as elicited from the present study. Advocacy through mass media and sustenance of behavior change communication also needed for higher IUD utilization in both rural and urban area. DOI: http://dx.doi.org/10.3329/seajph.v3i2.20036 South East Asian Journal of Public Health Vol.3(2) 2013: 30-34